Estimation of Seismic Economic Loss and Downtime of Precast Concrete Frames with "Dry" Connections. Issue 3 (November 2021) - Wu, Chenhao
Abstract: The seismic loss of buildings comes not only from the damaged structural components. Much more loss may be induced by non-structural components, the demolition loss and social impacts associated with excessive downtime. One of the main characteristics of a resilient city is that the buildings in the city should be able to recover to their pre-earthquake functionalities with minimized economic loss and downtime. For this purpose, a comparative study regarding seismic economic loss and downtime is conducted between the conventional cast-in-situ reinforced concrete frames (RCFs) and precast concrete frames (PCFs) with "dry" connections. The results show that the PCFs with prestressed tendons (PTs) can effectively reduce demolition loss given their extraordinary self-centering capacity provided by PTs. By adding web friction devices at the beam ends, the economic loss of structural components and drift-sensitive non-structural components can be effectively reduced. The downtime of PCFs is reduced at given hazard levels compared with RCF given their rapid repair speed and easy assemblage. In view of the rapid post-earthquake repair and lower earthquake loss, the PCFs are worth further investigation and application to develop resilient cities.